Bangladesh development debates : perspectives from policy dialogues, v. 2 - Centre for Policy Dialogue (Bangladesh) (Dhaka : Pathak Shamabesh Book : Centre for Policy Dialogue, 2002)
Contributed articles.
Includes index.
Keywords: Bangladesh -- Economic policy; South Asia -- Economic conditions